2020
DOI: 10.2166/nh.2020.156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ENSO-based upstream water withdrawals for irrigation on downstream water withdrawals

Abstract: Abstract In the Southeast US, El Niño Southern Oscillation (ENSO), climate variability phenomena affect the quantity of water that is available for irrigation. The goals of this study were to determine the effect of upstream surface water withdrawals for irrigation on the quantity of water available for irrigation in downstream areas as a function of the ENSO phase and quantify the watershed area that can be irrigated using water withdrawn from streams in an ecol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Many states require new water permits to be justified assuming whole allotted water as “used” (Sheer, 2010), but this may not always happen in practice. In the short term, exempt over‐allocated users may not result in a gap between water demand and water supply but remains a red flag for potential conflict (Owen, 2014; Sangha, Lamba, & Kumar, 2020). However, due to the limited temporal extent of the model simulation, there is possibility for more extreme drought years which are not captured in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Many states require new water permits to be justified assuming whole allotted water as “used” (Sheer, 2010), but this may not always happen in practice. In the short term, exempt over‐allocated users may not result in a gap between water demand and water supply but remains a red flag for potential conflict (Owen, 2014; Sangha, Lamba, & Kumar, 2020). However, due to the limited temporal extent of the model simulation, there is possibility for more extreme drought years which are not captured in this analysis.…”
Section: Discussionmentioning
confidence: 99%
“…ENSO‐neutral, the third episode, is a phase between these two extreme phases (Australia Bureau of Meteorology, 2012). El Niño and La Niña can both have global impacts on weather, climate, wildfires, ecosystems, and economies (Capa‐Morocho et al ., 2016; Correia Filho et al ., 2019; Hooshyaripor et al ., 2019; Sangha et al ., 2020). Moreover, it has shown that ENSO affects the frequency and intensity of droughts (Varikoden et al ., 2015; Rivera et al ., 2018; Sobral et al ., 2019) and floods (Dilley and Heyman, 1995; Sun et al ., 2015; Saghafian et al ., 2017).…”
Section: Introductionmentioning
confidence: 99%